HUBUNGAN GAYA HIDUP DENGAN KEJADIAN HIPERTENSI DI POLI KLINIK PENYAKIT DALAM RUMAH SAKIT ACHMAD MOCHTAR BUKITTINGGI TAHUN 2015 - Putra, Yuhendri; Kasrin, Rinawati; Kurnia Sari, Yade (LPPM Universitas Prima Nusantara Bukittinggi, 2015)
Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries continuously over a period. several risk factors that can take into severe hypertension, among other things: stress, obesity, food containing salt, high cholesterol, preserved foods, meat, fruit durian, cigarettes, coffee, family history or genetic and age. Most of it is an indicator of an unhealthy lifestyle. Lifestyle is a pattern of life which describes the overall self interacts with its environment. The purpose of this study was to determine the relationship between lifestyle with hypertension. The sampling technique accidental sampling as many as 95 respondents. The independent variable in this study is a lifestyle, while the dependent variable was the incidence hipertensi Hasil univariate analysis obtained more than half of respondents (51.6%) who have a healthy lifestyle and more than half of respondents (52.6%) who had hypertension. Bivariate analysis results There is significant correlation between lifestyle with hypertension (p = 0.003 and OR = 3.937). So lifestyle is associated with the incidence of hypertension. For it is expected to further research to examine the other variables.